Boron-doped onion-like carbon with enriched substitutional boron: the relationship between electronic properties and catalytic performance. Issue 43 (30th September 2015) - Lin, Yangming; Zhu, Yansong; Zhang, Bingsen; Kim, Yoong Ahm; Endo, Morinobu; Su, Dang Sheng
Abstract : Boron-doped onion-like carbon is developed as a novel electrocatalyst. The detailed relationship between electronic properties and catalytic performance is explored. Abstract : Incorporating heteroatoms into onion-like carbon (OLC, average size ∼5 nm) with a fullerene-like structure and investigating its peculiar properties are fascinating challenges. Here, we present straightforward fabrication of doped OLC samples with a high concentration of boron (0.63–4.57 at%) via a high-temperature thermal diffusion method. The highest proportion of substitutional boron of the boron species reaches 29%, which far exceeds most of the reported boron-doped carbon materials. The influence of boron on the fullerene-like layers and electronic properties of OLC is systematically investigated using Raman spectroscopy with different excitation energies (1.58–3.8 eV) and ultraviolet photoelectron spectroscopy (UPS). The as-prepared boron-doped OLC samples exhibit a perfect four-electron process for the oxygen reduction reaction (ORR), which is similar to commercial Pt/C. It is worth noting that the intrinsic relationship between the electronic properties and catalytic performance of doped samples is explored based on experimental studies instead of theoretical calculations. The results indicate that the lower work function, lower valence band edge and higher density of states (DOSs) of doped OLC are crucial to improve the catalytic performance. Our work can provide valuable information on the design of doped metal-free materials and give new evidence for enhanced ORR activity associated with heteroatom doping and electronic properties.